2020
DOI: 10.1038/s41419-020-2688-5
|View full text |Cite
|
Sign up to set email alerts
|

Calpain system is altered in survival motor neuron-reduced cells from in vitro and in vivo spinal muscular atrophy models

Abstract: Spinal muscular atrophy (SMA) is a severe neuromuscular disorder caused by loss of the survival motor neuron 1 (SMN1) gene. SMA is characterized by the degeneration of spinal cord motoneurons (MNs), progressive skeletal muscle atrophy, and weakness. The cellular and molecular mechanisms causing MN loss of function are only partially known. Recent advances in SMA research postulate the role of calpain protease regulating survival motor neuron (SMN) protein and the positive effect on SMA phenotype of treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Indeed, we can report that co-treatment with BLD-2736 and chloroquine produced an increase in LC3II/GAPDH compared to treatment with BLD-2736 or chloroquine alone, indicating increased synthesis of LC3II following treatment with BLD-2736 [55]. These findings align with existing reports, from our team and others, that calpain inhibition, via treatment with exogenous calpain inhibitor compounds or overexpression of calpastatin, can activate clearance of accumulated proteins via increasing the activity of the autophagy protein quality control pathway [43,46,47,57,58]. Whilst it may be questioned whether the treatment with BLD-2736 may have instead decreased full-length ataxin-3 through effects on the expression of EGFP-ataxin-3 via an effect on transcription, we previously demonstrated that treatment with calpeptin decreased the presence of full length human ataxin-3 protein, without altering the levels of human ataxin-3 mRNA, and that this effect was prevented by cotreatment with the autophagy inhibitor, chloroquine [43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, we can report that co-treatment with BLD-2736 and chloroquine produced an increase in LC3II/GAPDH compared to treatment with BLD-2736 or chloroquine alone, indicating increased synthesis of LC3II following treatment with BLD-2736 [55]. These findings align with existing reports, from our team and others, that calpain inhibition, via treatment with exogenous calpain inhibitor compounds or overexpression of calpastatin, can activate clearance of accumulated proteins via increasing the activity of the autophagy protein quality control pathway [43,46,47,57,58]. Whilst it may be questioned whether the treatment with BLD-2736 may have instead decreased full-length ataxin-3 through effects on the expression of EGFP-ataxin-3 via an effect on transcription, we previously demonstrated that treatment with calpeptin decreased the presence of full length human ataxin-3 protein, without altering the levels of human ataxin-3 mRNA, and that this effect was prevented by cotreatment with the autophagy inhibitor, chloroquine [43].…”
Section: Discussionsupporting
confidence: 90%
“…We found that treatment with calpeptin resulted in decreased abundance of, not only the ataxin-3 cleavage fragments, but also the fulllength ataxin-3 protein. Our study, and others, have demonstrated that calpain inhibition can produce a robust induction of autophagy [43,[46][47][48][49][50], which may contribute to the therapeutic potential of calpain inhibitor compounds. Therefore, additional studies are required to confirm whether the beneficial effect of calpain inhibition seen in these studies is indeed inhibition of ataxin-3 cleavage, or perhaps another effect of calpain inhibition, such as induction of autophagy, leading to active degradation of toxic protein aggregates.…”
Section: Introductionsupporting
confidence: 58%
“…SMA and non-affected control human iPSC cells (from Coriell Institute, see Materials and Methods) were differentiated to MNs following the protocol described [ 26 , 27 ] (Fig. 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Beclin 1 is the substrate of several proteases including caspases and calpain [ 45 , 46 ]. It is known that caspase and calpain pathways are deregulated in Smn-reduced cells in SMA pathology [ 27 , 47 , 48 ]; therefore, the activation of these pathways in muscle cells could be the basis for a decrease in Beclin 1. Studies of muscle-specific SMN reduction may help to elucidate the contribution of autophagy, apoptosis, and calpain pathways on SMA muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation